Efficacy and Safety of Tocilizumab for Polyarticular‐Course Juvenile Idiopathic Arthritis in the Open‐Label Two‐Year Extension of a Phase III Trial. Issue 3 (9th February 2021) - Brunner, Hermine I.; Ruperto, Nicolino; Zuber, Zbigniew; Cuttica, Rubén; Keltsev, Vladimir; Xavier, Ricardo M.; Burgos‐Vargas, Ruben; Penades, Inmaculada Calvo; Silverman, Earl D.; Espada, Graciela; Zavaler, Manuel Ferrandiz; Kimura, Yukiko; et al.
Abstract : Objective: To report the 2‐year efficacy and safety of tocilizumab (TCZ) in patients with polyarticular‐course juvenile idiopathic arthritis (JIA). Methods: Patients ages 2–17 years with active polyarticular‐course JIA, in whom treatment with methotrexate was unsuccessful, received 16 weeks of open‐label intravenous TCZ in part 1 (once every 4 weeks: 8 mg/kg or 10 mg/kg for body weight [BW] <30 kg; 8 mg/kg for BW ≥30 kg). Assessments were based on the JIA–American College of Rheumatology (ACR) response (defined as percentage of improvement in ≥3 of the 6 JIA core response variables [CRVs]). Patients with at least a JIA‐ACR30 response (defined as ≥30% improvement in ≥3 of the 6 JIA CRVs without worsening in >1 of the remaining JIA CRVs by >30%) at week 16 were randomly assigned (1:1) to receive TCZ or placebo in part 2. Patients remained in part 2 until either week 40 or the occurrence of JIA flare. Upon starting part 3, all patients received open‐label TCZ. At week 104 of the study, efficacy was assessed using JIA‐ACR50/70/90 response rates (defined as 50%, 70%, or 90% improvement, respectively), achievement of inactive disease, and the Juvenile Arthritis Disease Activity Score in 71 joints (JADAS‐71). Safety was assessed in the all‐exposure population per 100 patient‐years of exposure. Results: Overall, 188 patients entered part 1, 166 patients entered part 2, and 160 patients entered part 3. By week 104, among the 188 patients in the modified intent‐to‐treat group who received TCZ, JIA‐ACR50/70/90 response rates were 80.3%/77.1%/59.6%, respectively, the median JADAS‐71 score decreased from 3.6 at week 40 to 0.7 at week 104, 51.1% of patients had achieved inactive disease, and 31 of 66 patients who had been receiving glucocorticoids discontinued them. Adverse event (AE) and serious AE rates were 406.5 per 100 patient‐years and 11.1 per 100 patient‐years, respectively. The infection rate was 151.4 per 100 patient‐years, and the serious infection rate was 5.2 per 100 patient‐years. Conclusion: Patients treated with TCZ for polyarticular‐course JIA showed high‐level disease control for up to 2 years. The TCZ safety profile was consistent with that previously reported.